2003
DOI: 10.4049/jimmunol.170.7.3799
|View full text |Cite
|
Sign up to set email alerts
|

A Common Mucosal Chemokine (Mucosae-Associated Epithelial Chemokine/CCL28) Selectively Attracts IgA Plasmablasts

Abstract: IgA immunoblasts can seed both intestinal and nonintestinal mucosal sites following localized mucosal immunization, an observation that has led to the concept of a common mucosal immune system. In this study, we demonstrate that the mucosae-associated epithelial chemokine, MEC (CCL28), which is expressed by epithelia in diverse mucosal tissues, is selectively chemotactic for IgA Ab-secreting cells (ASC): MEC attracts IgA- but not IgG- or IgM-producing ASC from both intestinal and nonintestinal lymphoid and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
210
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(219 citation statements)
references
References 29 publications
9
210
0
Order By: Relevance
“…We have indeed demonstrated that a substantial fraction of plasma cells derived from human bone marrow expresses CCR10 and efficiently migrates to its ligands CCL27 and CCL28 (25). Furthermore, Butcher and his colleagues (26,27) have demonstrated that IgA-ASCs present in various mucosal tissues commonly express CCR10. We have also demonstrated that CCR10 plays an important role in the homing of IgA-ASCs into the small intestine and colon (11).…”
Section: -Dihydroxyvitamin D 3 Induces Ccr10 Expression In Terminmentioning
confidence: 92%
See 2 more Smart Citations
“…We have indeed demonstrated that a substantial fraction of plasma cells derived from human bone marrow expresses CCR10 and efficiently migrates to its ligands CCL27 and CCL28 (25). Furthermore, Butcher and his colleagues (26,27) have demonstrated that IgA-ASCs present in various mucosal tissues commonly express CCR10. We have also demonstrated that CCR10 plays an important role in the homing of IgA-ASCs into the small intestine and colon (11).…”
Section: -Dihydroxyvitamin D 3 Induces Ccr10 Expression In Terminmentioning
confidence: 92%
“…It is known that IgA-ASCs in the intestinal tissues frequently express CCR9 and/or CCR10 (26,27). Recently, Mora et al (39) have demonstrated that DCs in the gut-associated lymphoid tissues (GALT), but not those in the nonmucosal lymphoid tissues, induce the expression of ␣ 4 ␤ 7 and CCR9 in activated B cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver lymphocytes were obtained by mincing the tissue, mechanically dispersing it through a wire mesh, and isolating the lymphocytes on a 33% Percoll (GE Healthcare Bio-Sciences) gradient. Lung lymphocytes were isolated by digesting lungs in 300 U/ml type VIII collagenase (Sigma-Aldrich) for 30 min as described previously (54). Lymphocytes were resuspended in RPMI 1640 with 10% FCS and allowed to recover in a CO 2 incubator for Ͼ1 h before chemotaxis experiments.…”
Section: Cell Isolationmentioning
confidence: 99%
“…For example, in mice only DC derived from Peyer's patches and mesenteric lymph nodes were able to induce expression of α 4 β 7 + and CCR9 + on CD8 + T cells leading to site specific homing of these effector cells to the small intestinal lamina propria [74,109]. CCR9, the receptor for the thymus-expressed chemokine (TECK, CCL 25), is expressed on effector B and T cells and mediates the selective migration of these effector cells to the small intestine in humans and mice [19,87,120]. Interestingly, CCR9 -/-knockout mice display reduced numbers of plasma cells in the small intestinal lamina propria and impaired ability to respond to oral vaccination [119].…”
Section: General Considerations For Mucosal Vaccinesmentioning
confidence: 99%